التفسير باللازم عند الإمام الطاهر بن عاشورـ نماذج مختارة ـ - كرطي, كوثر; فالح, بدرة (University of eloued جامعة الوادي, 2021)
"تناول هذا البحث دراسةَ التفسير باللازم عند الإمام ابن عاشور من خلال بعض النماذج المختارة، والتي تمّت دراستها بعد استقراء جزئي من خلال تفسيره "" التحرير والتنوير "". لقد حاول هذا البحث عرض بعض ما يخصّ التفسير باللازم عموما: كتعريفه وبيان أهميته وضوابطه، وبعض ما يخصّ تطبيقات الإمام ابن عاشور له في تفسيره خصوصا. ولقد توصّل هذا البحث إلى نتائج أهمها: أنّ الإمام حاول استنباط أي لازم له أثر في التفسير متى وُجد ملتزما في ذلك بإتباع ضوابط التفسير باللازم ما أمكنه. وباقي النّتائج المُتَوَصَّل إليها مذكورة في خاتمة البحث.  ""This research make ""THE EXPLANATION of NECESSARY ""at ""AL IMEM IBN ACHOURE"" from a few selected forms and when that studied after a partial induction from his explanation ""AL TAHRIRE and AL TANWIRE"". This research essay an display of the explanation of necessary in general like : its definition ,its importance, its controls, and a few application of AL IMEM IBN ACHOURE specially in his explanation. This research get there to necessary results: AL IMEM IBN ACHOURE essay an elicit any necessary that make sure in his explanation, in when it is found required with real control. And the rest of results is mentioned on the end of research.
علوم قرآن
Keywords: التفسير باللازم ،الإمام ابن عاشور.; THE EXPLANATION of NECESSARY ، AL IMEM IBN ACHOURE